A Lightweight Identity Authentication Protocol for Nano-Scale IoT Devices - Radhi, Batool Mohammed; Ataalla, Abdalrahman Fatikhan; Alsayednoor, Huda Mohammed; Al-Shareeda, Mahmood A.; Almaayah, Mohammed Amin; Obeidat, Mansour (Engineering, technology & applied science research, 2025)
The nano-scale Internet of Things (nano-IoT) is ushering in a new era of applications in areas such as biomedical sensing, smart dust, and embedded environmental monitoring. Unfortunately, the utilization of nano-devices is barely feasible because of their very limited energy, computation, memory, and communication bandwidth, making existing cryptographic authentication methods infeasible. This study introduces an ultra-lightweight identity authentication protocol designed for nano-IoT systems with limited resources. The proposed protocol uses symmetric key cryptography, one-way hash functions, and XOR operations to achieve mutual authentication with low computational and communication costs. A highly modular architecture is proposed, consisting of 4 main stages: cryptographically secure pre-loading of credentials, a hash-based mutual authentication scheme, a stateless session update mechanism using hash chains and nonces, and a gateway-level revocation enforcement model. In contrast to PUF- or ECC-based protocols, the proposed protocol is extremely resistant to impersonation, replay, man-in-the-middle, desynchronization, and side-channel attacks without requiring special hardware. Simulations in nano-IoT settings show that the proposed protocol is more than 8 times faster and 11 times more energy-efficient than public-key-based algorithms, with high scalability and robust security. This study offers a solid basis for the secure bootstrapping of the forthcoming nano-IoT in dynamic, low-power, and latency-constrained environments.